2023
DOI: 10.3390/s23031246
|View full text |Cite
|
Sign up to set email alerts
|

The Application of SWAT Model and Remotely Sensed Products to Characterize the Dynamic of Streamflow and Snow in a Mountainous Watershed in the High Atlas

Abstract: Snowfall, snowpack, and snowmelt are among the processes with the greatest influence on the water cycle in mountainous watersheds. Hydrological models may be significantly biased if snow estimations are inaccurate. However, the unavailability of in situ snow data with enough spatiotemporal resolution limits the application of spatially distributed models in snow-fed watersheds. This obliges numerous modellers to reduce their attention to the snowpack and its effect on water distribution, particularly when a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…We applied a methodology akin to that used by [10,11,34,49] for calibrating snow parameters to simulate SWE and streamflow in the study basin. However, in the absence of in situ data in the study basin, we utilized two newly developed datasets as reference data for snow parameters calibration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied a methodology akin to that used by [10,11,34,49] for calibrating snow parameters to simulate SWE and streamflow in the study basin. However, in the absence of in situ data in the study basin, we utilized two newly developed datasets as reference data for snow parameters calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate parameter estimation can lead to more realistic internal model dynamics and associated hydrological characteristics [30,31], ultimately enhancing the overall representation of catchment behaviour. Prior research has demonstrated the effectiveness of using remotely sensed data to implement and calibrate hydrological models [32][33][34]. The issue of model equifinality, where multiple parameter sets can produce equally good model performance, introduces uncertainty that can undermine the reliability of hydrological models in forecasting future water resources, especially in mountainous regions where snow processes significantly influence the hydrological cycle [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research area is located in Jiawang District in the northeast of the main urban area of Xuzhou City (34 1a), covering an area of 496.59 km 2 . It is located in the transitional zone between the North China Plain and the alluvial plain of the Yellow River, characterized by low hills, hillside plains, and alluvial plains.…”
Section: Study Areamentioning
confidence: 99%
“…In recent years, various pollutants stemming from agricultural cultivation, aquaculture, urban development, and other land-use practices have been introduced into water bodies as non-point source pollution through diverse surface-loading mechanisms, leading to water eutrophication [2,3]. After many years of research, the riparian vegetation buffer zone adopted in the process of material flow has been identified as a method with low cost, high efficiency, easy operation, and the most natural ecology [4].…”
Section: Introductionmentioning
confidence: 99%